Perú: comunicación y diálogos Interculturales - Pedraglio, Santiago (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
Nearly 500 years ago, the “Cajamarca encounter” between the Spanish conquerors and the Inca Atahualpa symbolized the lack of communication Peru was founded on. This event decisively conditioned the power structure during colonial times and even later in the republic. However, during this prolonged period, many indigenous and Afro-descendants Peruvian cultures, subordinate and marginalized, have experienced dissimilar processes of intercultural communication. There is a growing back and forth flow of communication between cultures considered subordinate and hegemonic. There also are  multiple contacts between indigenous cultures and in-between these and others, such as the Afro-descendant. This process of communication –and, simultaneously, affirmation of cultural identities– has gained a new impetus: it unfolds vigorously in rural areas and in cities. Moreover, cultural identities have ceased to exclusively identify with vernacular languages. The State has incorporated some of this; nevertheless, much remains to be done.

La incomunicación original sobre la que se fundó el Perú, simbolizada por el momento del “encuentro” de Cajamarca, entre los conquistadores españoles y elinca Atahualpa, hace cerca de 500 años, condicionó de manera decisiva la organización del poder colonial e, incluso, posteriormente, el poder republicano.Sin embargo, durante este prolongado periodo las diversas culturas indígenasy afrodescendientes peruanas, marginadas y subordinadas, han vivido disímilesprocesos de comunicación intercultural. Crece una comunicación de ida y vueltaentre las culturas consideradas subordinadas y las hegemónicas, y son múltipleslos contactos entre culturas indígenas, y entre estas y otras, como la  afrodescendiente. Este proceso de comunicación —y, simultáneamente, de afirmación de identidades culturales— ha cobrado un nuevo ímpetu: se despliega con vigor en las zonas rurales y en las ciudades. Es más, las identidades culturales ya dejaron de identificarse exclusivamente con las lenguas originarias. El Estado ha recogido algo de todo esto; sin embargo, todavía queda mucho por andar.
Communication and Intercultural Dialogues: a Peruvian case study
Keywords: Conquista española; Perú; Incomunicación; Diálogo; Identidades; Inteculturalidad; Estado; https://purl.org/pe-repo/ocde/ford#5.09.01